IMPLEMENTASI MESIN INFERENSI FUZZY (STUDI KASUS SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT TANAMAN CABE MERAH) - Wilis Kaswidjanti (Telematika, 2011)
Research was conducted based on the need for a tool for farmers in determining disease in red chilli plants and how to control it so as not not wrong in taking peptisida. The tool is an expert system which in addition to diagnosis, the system is expected to provide suggestions for control. Basically the software consists of two main parts, namely the input knowledge base, and the consultation. Decisions taken by using the rules. Inference method used is the fuzzy inference method with defuzzyfication using max-min method and the center average. The output of this software are the types of diseases that attack plants and its control in accordance with the advice of the devastation wrought on the red chilli plants.